Synthesis and characterization of slow pyrolysis pine cone bio-char in the removal of organic and inorganic pollutants from aqueous solution by adsorption: Kinetic, equilibrium, mechanism and thermodynamic - Dawood, Sara; Sen, Tushar; Phan, Chi (Elsevier BV, 2017)
Pine cone bio-char was synthesized through slow pyrolysis at 500 °C, characterized and used as an effective adsorbent in the removal of organic Methylene Blue (MB) dye and inorganic nickel metal (Ni(II) ions from aqueous phase. Batch adsorption kinetic study was carried out by varying solution pH, dye concentration, temperature, adsorbent dose and contact time. Kinetic and isotherm models indicates that the adsorption of both adsorbates onto pine cone bio-char were mainly by chemisorption. Langmuir maximum adsorption capability was found to be 106.4 and 117.7 mg/g for Methylene Blue (MB) and nickel ions (NI(II) respectively. Thermodynamic parameters suggested that the adsorption was an endothermic and spontaneous. These results indicate the applicability of pine cone as a cheap precursor for the sustainable production of cost-effective and environmental friendly bio-char adsorbent.